Resonant Leadership Style As A Moderating Variable Of The Influence Of Human Resource Information System On Employee Performance - Muhammad Risal Tawil; Teguh Setiawan Wibowo; Rasty Yulia; Dikky Mooy; Muhammad Syafri (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study is a quantitative study with an explanatory approach, namely an approach that relies on research to the nineteenth, twentieth, and twenty-first as the main material for building research foundations, building hypotheses, and proving hypotheses in this study. The data used in this study is quantitative data that researchers obtain directly or are also commonly referred to as primary data obtained from Zuri Group hotel employees spread throughout Indonesia as many as two hundred and fifty employees. The data obtained by the researcher were distributed through an online questionnaire containing ten questions with five choices including the choice of strongly agree, the choice of agree, the choice of so-so, the choice of disagree, and the choice of strongly disagree. The data obtained by the researcher were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the Human Resource Information System variable can have a positive relationship direction and significant influence on Employee Performance and the Resonant Leadership Style variable can strengthen the influence of the Human Resource Information System variable on Employee Performance. The results of the second row of the third table above show that the Human Resource Information System variable can have a positive relationship direction and significant influence on Employee Performance can be accepted because the P-Values ​​are positive and below the significance level of 0.05, namely 0.004. Based on these results, it can be concluded that the higher the Human Resource Information System, the higher the Employee Performance. In the next row, the Resonant Leadership Style variable can also moderate the influence of the Human Resource Information System variable on Employee Performance because the P-Values ​​are positive and below the significance level of 0.05, namely 0.000, more significant than direct testing of 0.004. Thus it can be concluded that the first and second hypotheses in this article can be accepted.